AUTHENTIC LEADERSHIP: DEVELOP THE LEADER WITHIN - Yasinski, Lesia (Operating Room Nurses Association of Canada Journal, 2014)
Great leadership usually starts with a willing heart, a positive attitude, and a desire to make a difference. Strong leadership is important, in today’s health care climate, to ensure optimal patient outcomes and the fostering of future generations of knowledgeable, motivated and enthusiastic perioperative nurses. This article will explore key elements necessary for the development of authentic leadership. While highlighting the role that personal development plays in leadership skills, this article will also discuss ways to cultivate authenticity in leadership. The following questions will be addressed: What is authentic leadership? How does one become an authentic leader?